Rate of severe and fatal infections in a cohort of patients with interstitial lung disease associated with rheumatoid arthritis: a multicenter prospective study - Mena-Vázquez, Natalia; Redondo-Rodriguez, Rocío; Rojas-Gimenez, Marta; Romero-Barco, Carmen María; Fuego-Varela, Clara; Perez-Gómez, Nair; Añón-Oñate, Isabel; Castro Pérez, Patricia; García-Studer, Aimara; Hidalgo-Conde, Ana; Arnedo Díez de los Ríos, Rocío; Cabrera-César, Eva; et al. (Frontiers in Immunology, 2024)
Objective: To describe severe infection, foci of infection, microorganisms, associated factors, and impact on mortality in patients with rheumatoid arthritis-associated interstitial lung disease (RA-ILD).Patients and methods: The study was based on a multicenter prospective cohort of patients with RA-ILD followed up from 2015 to 2023. The main outcome measures were incident severe infection and fatal infection. We evaluated infectious foci, etiologic agents, vaccination status, variables associated with lung function, and clinical-therapeutic variables in RA. The incidence rate (IR) for infection and mortality was calculated per 100 person-years, and 3 multivariate models were constructed to explore factors associated with infection.Results: We followed up 148 patients with RA-ILD for a median 56.7 months (699.3 person-years). During this period, 142 patients (96%) had at least 1 infection. A total of 368 infectious episodes were recorded, with an IR of 52.6 per 100 person-years. Of the 48 patients who died, 65% did so from infection. Respiratory infections were the most common first infection (74%), infection overall (74%), and fatal infection (80%) and were caused mostly by SARS CoV-2, Streptococcus pneumoniae, Pseudomonas aeruginosa, and influenza A virus. The factors associated with an increased risk of infection and death in patients with RA-ILD were age, inflammatory activity, and therapy with corticosteroids and immunosuppressants. Conclusion: Patients with RA-ILD have a high risk of serious infection, especially respiratory infection. Infection develops early, is recurrent, and is frequently fatal. The presence of associated factors such as advanced age, joint inflammation, and treatment highlight the importance of integrated and preventive medical care. Word Count: 4000.